2006
DOI: 10.1016/s0022-5347(05)00018-2
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Life Expectancy in Men With Clinically Localized Prostate Cancer

Abstract: Overall life expectancy can be predicted with a moderate degree of accuracy, sufficient for informing patient-clinician discussions but inadequate as the only determinant of the optimal management approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 15 publications
0
53
0
2
Order By: Relevance
“…Even nomograms using Gleason score in combination with extent of biopsy core involvement, pretreatment serum PSA levels, and clinical stage fail to adequately identify all patients at risk of developing biochemical recurrence [18]. Thus, molecular prognostic biomarkers independently predicting the biologic behavior and outcome of prostate cancer are the focus of many studies [19].…”
Section: Discussionmentioning
confidence: 99%
“…Even nomograms using Gleason score in combination with extent of biopsy core involvement, pretreatment serum PSA levels, and clinical stage fail to adequately identify all patients at risk of developing biochemical recurrence [18]. Thus, molecular prognostic biomarkers independently predicting the biologic behavior and outcome of prostate cancer are the focus of many studies [19].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 When determining which men are likely to benefit from definitive therapy for prostate cancer, patient life expectancy must be considered along with clinical stage, PSA and biopsy information. [3][4][5] Since men diagnosed with prostate cancer are unlikely to die of it, some groups suggested that the benefit of prostate cancer diagnosis is greatest when it leads to lifestyle changes that prevent or delay the competing causes of death. 6,7 However, in the RP population the nonprostate cancer causes of death after surgery remain unclear.…”
mentioning
confidence: 99%
“…[5, 7, 8] Four models presented risks of other cause mortality only after a treatment was already selected. [912] These estimates are clearly influenced by treatment selection. For instance, in the Walz et al model, a 65-year-old patient with 3 comorbidities would have a 10-year probability of death from other causes of 80% if treated by radiotherapy but 40% by surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Although they report concordance indices ranging from 0.60 – 0.84, the tools with higher discrimination, those of Walz et al [10] and Cowen et al [12], both required a treatment to be selected to obtain predictions…”
Section: Discussionmentioning
confidence: 99%